THE EVIDENCE BASE OF QUALITY STATEMENTS ON ADVANCED DEMENTIA: A SYSTEMATIC REVIEW. Issue 1 (1st March 2014) - Candy, B; Elliott, M; Jones, L; Sampson, E
Abstract : Introduction: The National Institute for Health and Care Excellence (NICE) clinical guideline on dementia highlighted how people with dementia may not be able to access good quality palliative care (NICE 2007). Subsequently, the NICE Quality Standards Programme for Dementia provided quality statements for commissioners to guide the care of those with advanced dementia. However, the literature review supporting these statements identified little empirical evidence behind these. Since then new research on end of life care in dementia has been published. Aim(s) and method(s): To undertake a systematic review of the current evidence relevant to three NICE quality statements on care of people with advanced dementia: (1) advanced care planning; (2) assessment of palliative care needs; (3) a named care co-ordinator. We are searching four databases including EMBASE and other sources including expert consultation. We seek high quality quantitative and qualitative research. For the quantitative evidence, in our summation we are prioritising studies of comparative design. If there are randomised trials we will use as appropriate meta-analysis to combine the trials. For the qualitative evidence we are using thematic synthesis approaches as appropriate. All key stages are undertaken in duplicate. Results: We will have completed our review by March 2014 and will summarise how well each quality statement is supported by evidence. Conclusion(s): This review will identify how robust these commissioning statements are with respect to the evidence that underlies them. We will be able to make recommendations on how the quality standards may be improved and made more effective in day to day practice.